2022
DOI: 10.1002/jdn.10216
|View full text |Cite
|
Sign up to set email alerts
|

Skin‐to‐skin contact to support preterm infants and reduce NICU‐related stress

Abstract: Objective Hospitalization in the neonatal intensive care unit (NICU) with numerous painful medical interventions, being separated from parents, leads to the high risk of chronic stress for preterm infants. Today, many NICUs use more appropriate developmental care and pain management, but the early and long‐term outcomes of stress in these vulnerable infants require searching for more stress‐reducing interventions in neonatal care. The objective of the study was to investigate how skin‐to‐skin contact (SSC) can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 30 publications
(37 reference statements)
0
11
0
Order By: Relevance
“…Most of the studies covered the care between birth and discharge or birth to 72 hours,14 18–20 23 26 27 30 33–35 41 43 46 49 51–58 61 62 64 67 69–73 76 78–80 82–85 four studies reported on follow-up care at home,16 47 48 50 one on care during ground ambulance transport37 and five studies covered end-of-life care 25 36 42 72 84. We found no studies that reported on home birth.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…Most of the studies covered the care between birth and discharge or birth to 72 hours,14 18–20 23 26 27 30 33–35 41 43 46 49 51–58 61 62 64 67 69–73 76 78–80 82–85 four studies reported on follow-up care at home,16 47 48 50 one on care during ground ambulance transport37 and five studies covered end-of-life care 25 36 42 72 84. We found no studies that reported on home birth.…”
Section: Resultsmentioning
confidence: 89%
“…Of those 19, eight focused on overall parental experience with newborn care,22 27 30 32 38 42 43 45 the remaining eleven focused on specific aspects of care, such as kangaroo mother care (KMC) provision,37 41 discharge education,26 postnatal diagnoses,18 24 end of life care21 25 31 or home-based postnatal care 47 48 50. Additionally, 16 studies measured newborn experience during hospital stay through physiological markers or measures of pain and comfort during routine procedures such as skin-to-skin contact, bathing, cobedding or heel prick, among others 52–67. Only two articles focused on mistreatment of the newborn during the immediate postpartum period, both using an adapted version of the Bohren et al 68 typology of mistreatment (developed to measure maternal experience) 69 70…”
Section: Resultsmentioning
confidence: 99%
“…Early, prolonged, and frequent skin-to-skin care has been shown to have profound benefits to both the infant and the parent. 43 Positive auditory experiences, such as hearing the parents read 51 or sing, 52 have also been found to be beneficial to the infant and parents, Malin et al both in the short and long terms. Infant development is positively influenced as parental confidence and competence are increased.…”
Section: What Can We Do?mentioning
confidence: 99%
“…If the intervention is necessary, then we must ask, "What can be done to support this infant in a way that will reduce the level of discomfort or trauma that the infant experiences?" For example, when painful or stressful procedures are performed (eg, skin-breaking procedures), there is evidence that skin-to-skin holding, 43 non-nutritive sucking, especially with glucose or mother's milk, 49 and exposure to the odor of mother's milk 50 reduce pain and stress. Encouraging positive experiences while in the NICU can play an important role supporting the infant's emotional development to build trust.…”
Section: What Can We Do?mentioning
confidence: 99%
See 1 more Smart Citation